2000
DOI: 10.1074/jbc.275.17.12388
|View full text |Cite
|
Sign up to set email alerts
|

Heat-inactivated Proteins Managed by DnaKJ-GrpE-ClpB Chaperones Are Released as a Chaperonin-recognizable Non-native Form

Abstract: Chaperones of Thermus thermophilus cooperate in reactivation of heat-inactivated proteins. The protein, inactivated at a high temperature in a TDnaKJ-GrpE set, recovered its activity during subsequent incubation with TClpB at moderate temperature (Motohashi, K., Watanabe, Y., Yohda, M., and Yoshida, M. (1999) Proc. Natl. Acad. Sci. U. S. A. 96, 7184 -7189). Here, we report that the addition of chaperonin (Tcpn) at moderate temperature improves the yield of the TDnaKJ-GrpE-ClpBdependent reactivation. The trap-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…In eukaryotes, this cooperation helps yeast cells to recover from severe heat stress (8 -10), and in vitro experiments have shown that HSP104-HSP70 cooperation facilitates reactivation of the proteins that had been chemically denatured and aggregated (3). In prokaryotes, as we have demonstrated for chaperones from a thermophilic eubacteria, Thermus thermophilus, heatdamaged proteins were rescued by the cooperative chaperone functions of ClpB (bacterial HSP104), DnaK (bacterial HSP70), DnaJ, and GrpE (4,11). ClpB forms a homo-hexameric complex (580 kDa) as an active species and needs ATP hydrolysis for the function (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In eukaryotes, this cooperation helps yeast cells to recover from severe heat stress (8 -10), and in vitro experiments have shown that HSP104-HSP70 cooperation facilitates reactivation of the proteins that had been chemically denatured and aggregated (3). In prokaryotes, as we have demonstrated for chaperones from a thermophilic eubacteria, Thermus thermophilus, heatdamaged proteins were rescued by the cooperative chaperone functions of ClpB (bacterial HSP104), DnaK (bacterial HSP70), DnaJ, and GrpE (4,11). ClpB forms a homo-hexameric complex (580 kDa) as an active species and needs ATP hydrolysis for the function (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 85%
“…TDafA is a small protein necessary to assemble TDnaK and TDnaJ into K⅐J (20); TGrpE (22 kDa) is isolated as a homodimer (21)(22)(23). The stable K⅐J has been reported only for DnaK and DnaJ from T. thermophilus, but the chaperone function of K⅐J has been studied with a general interest because the current model for the mechanism of DnaK function assumes only transient but not stable interaction between DnaK and DnaJ (4,11,16,19,23). Related to this contention, the chaperone activity of uncomplexed TDnaK and TDnaJ (termed KϩJ) has been reported (14,23,24), but the difference from that of K⅐J is not clear.…”
mentioning
confidence: 99%
“…Only recently, it was recognized that certain chaperones are able to solubilize aggregated proteins in vivo. The concerted action of Hsp104, Hsp70, and Hsp40 in yeast (92) or of ClpB and DnaK in E. coli (94,211,214,347) recycles precipitated proteins into the folding pathway. Disaggregated material is released in a nonnative form that either can refold spontaneously or can be further processed by cellular chaperones.…”
Section: Stress Conditionsmentioning
confidence: 99%
“…Since a similar activity had previously been described for the cytosolic Hsp104 (10,11), the current view is that proteins of the ClpB subtype are mainly required for the protection of cellular protein function under severe stress conditions (7,12,13). Evidently, cellular proteins can be solubilized from heat-induced aggregates by ClpB-type chaperones and are released in a state that is recognized and stabilized by the Hsp70 system, which promotes further folding to the native conformation (8,11,14). A similar role in thermotolerance and stress protection has been suggested for the mitochondrial homolog Hsp78 (15,16).…”
mentioning
confidence: 99%